Aragonese voices in "Complete short stories" (2011) by Ramón Gil Novales - Nagore Laín, Francho (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
73 Aragonese voices that are recorded in Ramón Gil Novales Cuentos completos [Complete Stories] (2011) are collected in this work and the author's linguistic Aragoneseness is valued.
Keywords: aragonese voices; Ramón Gil Novales